2022
DOI: 10.3389/fimmu.2022.968799
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the gut-liver axis to the immune signaling pathway of NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the liver manifestation of metabolic syndrome and is the most common chronic liver disease in the world. The pathogenesis of NAFLD has not been fully clarified; it involves metabolic disturbances, inflammation, oxidative stress, and various forms of cell death. The “intestinal-liver axis” theory, developed in recent years, holds that there is a certain relationship between liver disease and the intestinal tract, and changes in intestinal flora are closely involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 175 publications
(202 reference statements)
0
10
0
Order By: Relevance
“…Particularly, the relationship between gut microbiota and NAFLD has garnered significant attention in research. It has been observed that the gut microbiota plays a pivotal role in the onset and progression of NAFLD through various mechanisms [ [24] , [25] , [26] ]. Dysbiosis in the gut microbiota increases intestinal permeability, allowing harmful substances like lipopolysaccharides to enter the bloodstream, triggering hepatic inflammation [ [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the relationship between gut microbiota and NAFLD has garnered significant attention in research. It has been observed that the gut microbiota plays a pivotal role in the onset and progression of NAFLD through various mechanisms [ [24] , [25] , [26] ]. Dysbiosis in the gut microbiota increases intestinal permeability, allowing harmful substances like lipopolysaccharides to enter the bloodstream, triggering hepatic inflammation [ [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been suggested that SIBO may contribute to the development of MASLD by inducing gut permeability and systemic inflammation, leading to the development of metabolic disorders, including insulin resistance (30)(31)(32). Also, gut microbiota differences between obese patients with or without MASLD has been previously reported by Jin and Xu (33), the gut microbiota composition was similar between obesity with MASLD and simple obesity, but the Faecalibacterium prausnitzii colony number was much lower in the obesity with MASLD than in the simple obesity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this enterohepatic circulation, the liver is constantly exposed to substances that originate from the gut ( 160 ). Furthermore, the association linking the gut and the liver, commonly called the “gut-liver axis,” has garnered increasing attention from researchers due to its pivotal role in preserving liver homeostasis and averting the onset of ailments ( 161 , 162 ). One common finding in several liver illnesses is that tight connections between adjacent intestinal epithelial cells are impaired with increasing intestinal permeability, indicating that substances coming from the gut have an impact on liver function ( 160 , 163 ).…”
Section: The Role Of the Microbiome In Liver Cancermentioning
confidence: 99%